University of Florida Potato Variety Trials Spotlight: 'Marcy' - Rodrick Z. Mwatuwa; Christian T. Christensen; Lincoln Zotarelli (EDIS)
This article introduces the potato variety, ‘Marcy’, which was developed at the University of Florida. ‘Marcy’ is a white-flesh and white-skinned fresh-market potato variety that has demonstrated high yield and good tuber characteristics. This 3-page fact sheet provides the general characteristics, season length and growth information, fertilization and planting instructions, as well as disease information for the potato variety, ‘Marcy’. Written by Rodrick Z. Mwatuwa, Christian T. Christensen, and Lincoln Zotarelli, and published by the Horticultural Sciences Department, March 2016.